Vulnerability of wheat production to climate change in India - Naresh Kumar, Soora; Aggarwal, Pramod K.; Swaroopa Rani, D.N.; Saxena, R.; Chauhan N; Jain S (Inter-Research Science Center, 2014)
The production of wheat, a crop sensitive to weather, may be influenced by climate change. The regional vulnerability of wheat production to climate change in India was assessed by quantifying the impacts and adaptation gains in a simulation analysis using the InfoCrop-WHEAT model. This study projects that climate change will reduce the wheat yield in India in the range of 6 to 23% by 2050 and 15 to 25% by 2080. Even though the magnitude of the projected impacts is variable, the direction is similar in the climate scenarios of both a global (GCM-MIROC3.2.HI) and a regional climate model (RCM-PRECIS). Negative impacts of climate change are projected to be less severe in low-emission scenarios than in high-emission scenarios. The magnitude of uncertainty varies spatially and increases with time. Differences in sowing time is one of the major reasons for variable impacts on yield. Late-sown areas are projected to suffer more than the timely-sown ones. Considerable spatial variation in impacts is projected. Warmer central and south-central regions of India may be more affected. Despite CO2 fertilization benefits in future climate, wheat yield is projected to be reduced in areas with mean seasonal maximum and minimum temperatures in excess of 27 and 13°C, respectively. However, simple adaptation options, such as change in sowing times, and increased and efficient use of inputs, could not only offset yield reduction, but could also improve yields until the middle of the century. Converting late-sown areas into timely-sown regions could further significantly improve yield even with the existing varieties in the near future. However, some regions may still remain vulnerable despite the adaptation interventions considered. Therefore, this study emphasises the need for intensive, innovative and location-specific adaptations to improve wheat productivity in the future climate.